The Position of Female Workers in the Labor Market in the Light of Activity and Employment Contracts - Győrváriné Tumpek, Gabriella (Acta Carolus Robertus, 2023)
The situation of female employees differs from that of men. Women have to deal with many forms of discrimination during their careers. In this area, the situation of employees raising small children is particularly difficult. In this study, we examine the labor market activity and the possible differences in the types of employment contracts and their possible causes by gender and overall.
Keywords: female workers; reintegration; disadvantage